EFFECT OF SOME ANTIBIOTIC ON SOME SPECIES OF SALMONELLA AND SHIGELLA ISOLATED FROM DIARRHEA CASES. - AFAF A. YOUSIF; ASAAD K.TALAL (مجلة جامعة الانبار للعلوم الصرفة, 2012)
This study included (50) Stool specimens which were collected from various age groups from (4 months to 50 years) of patients suffering from acute diarrhea (bloody and watery), from hospitals in Baghdad, These specimens were collected and cultured on enrichment, selective and differential media to detect the genera Shigella and Salmonella. Different biochemical tests were used to differentiate the isolates from other enteric bacteria. Results showed that 13 (59.09%) isolates out of (22) isolates were found belong to the genus Salmonella.(6) isolates S.typhimurium (27.27%), (4) isolates S.mesthamputum(18.18%) ,(2) isolates S.typhi(9.09%) and one isolate S.emek(4.55%).while the results showed that 9(40.91%)isolates were belong to Shigella Flexner. Different antimicrobial agents were used for antibiotic sensitivity and results showed that. All Shigella isolates (100%) were sensitive to (Ciprofloxacin, Nalidixic acid, Neomycin and Cephotaxime). And resistant (100%) to (Rifampicin, Ampicillin, and Amoxicillin). All Salmonella isolates (100%) were sensitive to (Ciprofloxacin).And resistant (100%) to(Chloramphenicol